Optimizing Traffic Management at Batam City Intersections: Analysis of Congestion Causes and Mitigation Strategies - Uswatun Azizatul Syarqiah; Yusra Aulia Sari (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Batam City is one of the centers of economic and trade activity in Indonesia which continues to experience rapid growth, causing a significant increase in traffic at city intersections. Traffic jams are a troubling problem for residents and visitors to the city. This research aims to identify the main factors that cause traffic jams at Batam city intersections and propose effective mitigation strategies. The research methods used include field surveys, traffic data analysis, and interviews with relevant stakeholders. The research results show that factors such as high vehicle volume, lack of coordination between traffic lights, and inadequate road infrastructure are the main causes of traffic jams at Batam city intersections. Based on these findings, several mitigation strategies are proposed, including improving coordination between relevant parties, adjusting traffic light patterns, and developing more efficient road infrastructure. Implementation of this strategy is expected to reduce traffic congestion and increase mobility in Batam City.